The prognostic value of admission serum uric acid for acute kidney injury: a two-center retrospective analysis - Huang, Shuo; Tang, Linger; Xu, Lingyi; Wang, Jinwei; Zheng, Xizi (Frontiers in Molecular Biosciences, 2025)
BackgroundAcute kidney injury (AKI) is a serious clinical syndrome, with elevated serum uric acid (SUA) recognized as a potential modifiable risk factor. Nonetheless, the association between reduced SUA and the risk of AKI, along with the modification by kidney function on this association, is not well understood.MethodsAll adult patients from Peking University First Hospital (PKUFH) were screened. The primary outcome was AKI during hospitalization. Restricted cubic spline (RCS) was utilized to examine the hypothesized non-linearity between AKI and SUA as a continuous variable. SUA was categorized into six groups and Poisson regression was applied to evaluate the association between SUA groups and AKI with 240–360 μmol/L as reference. Subgroup analysis was conducted in terms of estimated glomerular filtration rate (eGFR).ResultsAmong 62,775 patients enrolled from PKUFH, 1,866 patients developed AKI (3.0%). The RCS plot showed a U-shaped association between SUA and AKI. Compared with reference group, SUA ≤ 180 μmol/L and >480 μmol/L exhibited a 2.17-fold and a 4.86-fold increased risk of AKI in the unadjusted model. After full adjustment, the associated risk of AKI in SUA ≤ 180 μmol/L (RR 1.92, 95% CI 1.57–2.36) and SUA > 480 μmol/L (RR 1.17, 95% CI 1.03–1.34) was weakened but still demonstrated statistical significance. When stratified by eGFR, the U-shaped risk curve was much less steep in the subgroup with eGFR ≤ 45 mL/min/1.73 m2.ConclusionThis study reveals a U-shaped association between admission SUA and AKI risk. Kidney function is an important confounder for this association.